Polarisasi Armenianisme Dan Calvinisme Dalam Perspektif Kaum Injili - Sandra Monica, Gledys (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
Theological views are a part that is always the subject of discussion, even the most important debates throughout church history. Because the theological view becomes a reference for building standing power in Christ Jesus. Strong theology will produce an understanding perfect knowledge of the truth of God's Word. But it is undeniable that deep the development of God's church emerged developing theologies. The emergence of the theological schools of Calvinism and Arnanism basically have different theological contents from each other. In the development of the church, the appearance of two different views, Arminian and Calvinism, has indeed had a big impact because the theological content of these two views is different from one another. Evangelicals understand salvation as a complex subject to deal with. If Calvinism emphasizes God's sovereignty over humans, Armenism emphasizes human responsibility in responding to God's grace, then Evangelicals emphasize both. God and man have their respective roles in the experience of salvation. This certainly should not be interpreted allegorically, the role between God and humans must be seen as a whole Biblically. This article will discuss the polarization of Armenians and Calvinists from the perspective of evangelicals. The method used is to outline the core teachings of the Armenians, Calvinists and the perspectives of the Evangelicals on the doctrine of salvation.